Hippeastrum corm wax sealing material and preparation method thereof

By using a red bulb sealing material composed of hexafluoropropylene oligomer, beeswax, tackifier and high melting point paraffin, the problem of low flowering rate of existing wax sealing wax is solved, and a higher flowering rate and longer flowering period are achieved, while ensuring healthy growth and biocompatibility of the plants.

CN119744848AActive Publication Date: 2025-04-04HAINING HUAHAI HORTICULTURE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510009995.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The flowering rate of existing wax sealing red is limited. While reducing the evaporation and water loss of bulbs, the wax sealing technology also excessively inhibits its respiration effect, resulting in a decrease in flowering rate.

Method used

A red bulb sealing wax material is used, which consists of hexafluoropropylene oligomer, beeswax, tackifier and high melting point paraffin. It is prepared through a specific mixing and stirring process to improve the water and air transmittance of the sealing wax material, and ensure that the effective respiration of red bulb can be maintained after the wax sealing.

Benefits of technology

It significantly improves the flowering rate and flowering period of red bulbs, ensures healthy growth of plants after sealing, reduces the risk of fluorine diffusion, and improves the biocompatibility of sealing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the field of chemical synthesis, and particularly relates to a hippeastrum bulb wax sealing material and a preparation method thereof. The method comprises the following steps: (1) preparing the following raw materials in percentage by weight: 33 to 37 weight percent of hexafluoropropylene oligomer, 4 to 6 weight percent of beewax, 0.5 to 1.0 weight percent of tackifier and the balance of high-melting-point paraffin; (2) taking hexafluoropropylene oligomer and beeswax, mixing, stirring and reacting to prepare a first-section mixture; (3) mixing the first-section mixture with high-melting-point paraffin, stirring and reacting to prepare a second-section mixture; and (4) uniformly mixing the second-stage mixture with a tackifier, and naturally cooling to obtain the hippeastrum rutilum corm wax sealing material. The wax sealing material has good waterproof and antibacterial effects and mechanical protection effects, further optimizes the breathing environment of hippeastrum rutilum corm, improves the breathing effect, and improves the flowering rate and flowering period of the wax-sealed hippeastrum rutilum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical synthesis, and particularly relates to a wax sealing material for amaryllis bulbs and a preparation method thereof. Background Art

[0002] Amaryllis is a perennial herbaceous plant of the Amaryllis family, native to Peru and Brazil. It has a tall flower diameter, beautiful flower shape, large flowers, generous flower posture, and bright colors, and has a very high ornamental value. In southern China, it blooms from April to May, usually with 4 flowers per stem, a single flower blooms for about 7 days, and a single plant blooms for about 14 days. It is mostly used for fresh cut flower production, potted plants, and garden beautification. Amaryllis likes a warm, humid, and sunny environment. The bulbs of Amaryllis contain rich nutrients and water, which can provide support for the growth and flowering process of the plant after the dormant period. At the same time, under adverse conditions, the bulbs can also help the plant survive drought or other stress periods. Under a suitable growth environment, the bulbs can serve as the source of new leaves and pedicels, thereby promoting the birth of new plant tissues. Mature Amaryllis bulbs will give birth to daughter bulbs, which can be divided and propagated. Once the daughter bulbs are separated, they can be cultivated into new independent plants.

[0003] The wax-sealed amaryllis technique is a unique treatment method that allows amaryllis to grow and bloom normally in a soil-free environment. The technique involves wrapping the base of the bulb in a waxy substance, leaving only the flower buds at the top exposed. By waxing the bottom of the bulb, the wax-sealed amaryllis technique can effectively reduce water loss, ensuring that the water and nutrients inside the bulb can be continuously supplied to the developing flower buds. The wax-sealed design allows amaryllis to grow in an environment without soil, so there is no need for watering or fertilizing. This makes them ideal interior decorations with low maintenance requirements. Since there is no need for traditional planting, wax-sealed amaryllis can be easily placed anywhere in the home, such as on desktops, windowsills, etc., increasing the flexibility of arrangement. At the same time, the flowering rate of wax-sealed amaryllis is very high, almost reaching more than 90% under normal circumstances. Just place them under suitable temperature and light conditions, and you can see the flowers blooming in about 30 days.

[0004] However, with the increase in sales of wax-sealed amaryllis in recent years, the original flowering rate has gradually failed to meet the requirements, and many customers have reported that the flowering rate is insufficient. In this regard, our R&D personnel have discovered a more critical problem, that is, after the wax-sealed amaryllis is protected by wax sealing, it can lock and preserve the nutrients of the bulb itself, protect the bulb from common diseases such as insect pests and root rot, thereby maintaining the health of amaryllis, long flowering period, good flower color, and good protection. However, the wax seal will actually affect the respiration of amaryllis. This is mainly due to the wax sealing characteristics of wax-sealed amaryllis. During the wax sealing process, a blank part is set between 1.5 and 2.5 cm below the top of the bud of the bulb, and no protective wax is required to protect the bud of amaryllis and ensure the later budding and flowering effect. This is because the bulb itself will undergo normal respiration and evaporation. If too much blank part is retained, the moisture and nutrients of the bulb will be lost in advance. The main purpose is to limit the evaporation of wax-sealed amaryllis, because its nutrients are usually in excess, but after water loss, it cannot be replenished due to the characteristics of wax-sealed bulbs, which will also lead to a decrease in its flowering rate. Therefore, our company focused on how to inhibit the evaporation of amaryllis bulbs and improve their breathing environment. Summary of the invention

[0005] In order to solve the problems that the existing wax-sealed amaryllis has a limited flowering rate, and the existing wax-sealing technology reduces the evaporation water loss of the bulb while also excessively suppressing its respiration, the present invention provides an amaryllis bulb wax sealing material and a preparation method of the wax sealing material.

[0006] The main purpose of the present invention is: 1. It can further improve the water and air permeability of wax seals; 2. Ensure that the wax sealing material can more effectively maintain the effective respiration of Amaryllis after wax sealing; 3. It has good protective effect.

[0007] To achieve the above objectives, the present invention adopts the following technical solutions.

[0008] A method for preparing wax sealing material for Amaryllis bulbs, The method comprises: (1) The raw materials are prepared according to the following weight percentages: 33-37 wt% hexafluoropropylene oligomer, 4-6 wt% beeswax, 0.5-1.0 wt% tackifier, and the balance is high melting point paraffin; The high melting point paraffin wax is C28-C30 paraffin wax, which usually has a melting point of 61-65.5°C. The melting point of standard C28 paraffin wax is 61.1°C, and the melting point of standard C30 paraffin wax is 65.5°C. Unless otherwise specified, the present invention uses standard C28 paraffin wax with a melting point of 61.1°C. (2) mixing hexafluoropropylene oligomer and beeswax and stirring them to react to prepare a first-stage mixture; (3) mixing the first-stage mixed material with high-melting-point paraffin wax and stirring to react, thereby preparing a second-stage mixed material; (4) The second-stage mixed material and the viscosity enhancer are mixed evenly, and the mixture is cooled naturally to obtain the amaryllis bulb sealing wax material.

[0009] As a preference, The hexafluoropropylene oligomer in step (1) is prepared by the following method: The perfluoro compound, nitrile compound, polymer and metal fluoride salt are uniformly mixed in proportion, and stirred and thermally reacted under high pressure conditions to obtain the directionally prepared hexafluoropropylene oligomer.

[0010] As a preference, The perfluorinated compound is liquid hexafluoropropylene that has been subjected to a pressure treatment; The nitrile compound is acetonitrile; The polymer is polyethylene glycol; The metal fluoride salt is potassium fluoride; The perfluorinated compound, nitrile compound, polymer and metal fluoride salt are uniformly mixed in a mass ratio of 1.5:(4-6):(0.04-0.06):0.02.

[0011] As a preference, The high pressure condition is 1.0-1.2 MPa ambient pressure; The stirring thermal reaction is carried out at 75-85°C and 80-120 rpm for 40-45 min.

[0012] As a preference, The mixing and stirring reaction in step (2) is carried out at 0.3-0.4 MPa, 95-105°C, and at a speed of 40-60 rpm for 45-75 min.

[0013] As a preference, The mixing and stirring reaction in step (3) is carried out at 0.3-0.4 MPa, 120-140°C, and at a stirring speed of 70-90 rpm for 60-90 min.

[0014] As a preference, The uniform mixing in step (4) is carried out by stirring and mixing at a speed of 30 to 50 rpm for 60 to 90 min under the conditions of 0.3 to 0.4 MPa and 100 to 120°C.

[0015] A wax sealing material for amaryllis bulbs.

[0016] For the technical solution of the present invention, the actual research and development idea is to derive from the PTFE preservative film used for some plant transplants. PTFE preservative film is used in large quantities in protecting roots and branches during plant transplanting, and it has a good hydrophobic, water-proof and waterproof effect, but it has a certain air permeability, allowing gas to pass through. However, when it is used for amaryllis wax seal, there are many problems, such as how to mix it into the wax seal material, and its air permeability is too strong and may also cause the respiration of amaryllis bulbs to be too vigorous, causing its nutrients to be lost too quickly, resulting in shortened flowering period, flowering rate decline and other situations, and PTFE is usually difficult to build a stable supporting structure to form mechanical protection, and the most critical PTFE has the possibility of fluorine diffusion, fluorine has cytotoxicity, and has an impact on the metabolic process of plants and processes such as cell division, and although PTFE is very stable and has outstanding chemical resistance, it is still possible to diffuse fluorine in the case of direct contact and in the wax seal process of melt immersion plating. For example, in early experiments, the standard DGT (dynamic gel technique) was used to characterize the diffusion of fluorine in Amaryllis bulbs with the addition of PTFE or direct PTFE encapsulation, confirming the existence of this process.

[0017] After continuous attempts to select different materials, the technicians found that hexafluoropropylene copolymers have certain uniqueness. Because they have the characteristics of low melting point and low boiling point, the wax sealing process can be carried out at a lower temperature to reduce damage to the bulbs of Amaryllis. After mixing and solidifying, the double-layer structure of the separation layer and the support layer can be constructed through the synergy of the materials, which can effectively improve the gas exchange rate while ensuring good mechanical support protection and waterproofing.

[0018] In this regard, the present invention stirs hexafluoropropylene oligomers at a specific temperature and pressure to form a stable oligomer solution. Then, the solution is mixed with an additive in a specific ratio to prepare a first-stage mixed material. Then, the first-stage mixed material is further mixed with other ingredients to prepare a second-stage mixed material. Finally, the second-stage mixed material is stirred and mixed under suitable conditions to obtain a wax sealing material for Amaryllis bulbs. Through this preparation method, a wax sealing material with excellent physical and chemical properties can be obtained, which effectively protects Amaryllis bulbs and prolongs their shelf life.

[0019] The core lies in the nucleophilic addition reaction of hexafluoropropylene. Due to the significant electron-withdrawing properties of the fluorine atoms connected to its double bond, hexafluoropropylene is more susceptible to nucleophilic addition reactions than ordinary olefins. Liquid phase polymerization is a common method for preparing hexafluoropropylene oligomers. The process is usually carried out in a dry, non-protonic polar solvent containing a catalyst, and the reaction conditions include specific temperature and pressure. The product is mainly composed of hexafluoropropylene dimers and hexafluoropropylene trimers. By selecting different reaction conditions such as solvents and catalysts, oligomerization products with specific structures can be prepared. Hexafluoropropylene oligomers, including dimers and trimers, show excellent chemical stability and thermodynamic stability, so they can be used as solvents and media in special environments for the synthesis of polymers, intermediates and surfactants. Due to the difference in solubility of different isomers in solvents and their different reactivity with nucleophilic reagents, their application fields are also different. Due to the high activity of hexafluoropropylene dimers due to their carbon-carbon double bonds, they can react with a variety of nucleophilic reagents, and then synthesize a variety of fluorinated heterocyclic organics through a series of chemical reactions. Surfactants are substances that can reduce surface tension, usually composed of two groups, hydrophilic and hydrophobic. Fluorinated surfactants are types of hydrocarbon surfactants in which hydrogen is replaced by fluorine, and their fluorinated carbon chains have hydrophobic and oleophobic properties. Compared with ordinary hydrocarbon surfactants, fluorinated surfactants have higher efficiency and stronger stability, so they can be used as efficient fine chemicals in complex environments. The carbon atoms of hexafluoropropylene oligomers are connected to fluorine atoms. Due to the strong electronegativity of fluorine, unlike ordinary hydrocarbon olefins, they are not easy to react with electrophilic reagents. The carbon-carbon double bonds of hexafluoropropylene oligomers and the fluorine atoms connected to them have good activity. Through a series of reactions with nucleophilic reagents, fluorinated surfactants derived from hexafluoropropylene oligomers can be prepared.

[0020] Experiments show that under the condition of low room temperature, the polymerization process of hexafluoropropylene in acetonitrile shows a highly selective reaction to dimers. The intervention of polyethylene glycol further guides the selective conversion of hexafluoropropylene to trimers. Polyethylene glycol exists as both a solvent and a catalyst in the system of the present invention. Unlike acetonitrile, its addition in the experiment shows alternative selectivity, promotes the formation of highly polymerized (trimer) hexafluoropropylene, and improves its conversion rate to a certain extent. Combined with the relatively higher reaction temperature of the present invention, the selectivity of trimers in the oligomers of the present invention is significantly improved. As a fluorine-containing polymer, hexafluoropropylene oligomers themselves also have the possibility of fluorine diffusion, and trimers can more effectively inhibit the occurrence of fluorine diffusion than dimers. In other aspects, the study pointed out that when acetonitrile combines with halides to form complex salts, these complex salts can cooperate with cations in alkali metal fluorides to accelerate the separation of fluoride anions, which helps to increase the chemical reaction rate. The choice of acetonitrile as a solvent is mainly affected by the radius of the alkali metal fluoride cation. In this invention, different polymers of hexafluoropropylene oligomers are mixed and modified with paraffin wax to achieve the goals of enhancing material strength, improving wear resistance and improving chemical corrosion resistance. Considering the two dimensions of performance improvement and cost-effectiveness, blending modification has been proven to be the most promising method for modifying sealing wax materials.

[0021] The special structure of the obtained hexafluoropropylene oligomer gives it excellent performance. In the wax sealing material, the introduction of hexafluoropropylene oligomer significantly improves the thermal stability of the material. Due to its unique chemical structure, hexafluoropropylene oligomer can still maintain good physical and chemical properties at high temperatures, which is crucial for wax sealing materials. In practical applications, this material can withstand higher operating temperatures, thereby extending the service life of the wax sealing, and can still maintain good sealing performance in high temperature environments. In addition, the addition of hexafluoropropylene oligomers also gives the wax sealing material excellent waterproof and chemical corrosion resistance, allowing it to remain stable in harsh industrial environments and effectively protect the wax-sealed items from damage.

[0022] In the wax seal, the present invention also uses conventional paraffin components. When hexafluoropropylene oligomers are introduced into paraffin molecules, some C-H bonds will be converted into C-F bonds. Given that the electronegativity of fluorine atoms is significantly higher than that of hydrogen atoms, C-F bonds show stronger polarity and shorter bond lengths, which enhances the intermolecular interaction forces. In addition, the larger van der Waals volume of fluorine atoms leads to greater steric hindrance, making the molecules more closely arranged. The enhancement of these forces leads to increased intermolecular attraction, requiring more energy to overcome these interaction forces, thereby producing a more stable structure and support. Due to the steric hindrance effect of fluorine atoms, the fluorinated paraffin molecules are arranged more closely in the solid state, but also due to the support of the dimer, breathing micropores are formed, which increases the stability of the crystal structure and solves the problem of poor air permeability of paraffin. A more stable crystal structure means that a higher temperature is required to destroy this orderly arrangement, which leads to an increase in thermal stability. In order to accurately control the temperature of the wax melt, the present invention proposes a new type of amaryllis bulb wax seal and a preparation method thereof. The method comprises the following steps: first, paraffin wax and hexafluoropropylene oligomers in a specific ratio are selected for mixing. Then, by precisely controlling the heating temperature and time, it is ensured that the hexafluoropropylene oligomers can be evenly dispersed in the paraffin wax to form a stable mixture. During the mixing process, a specific stirring device is required to ensure the uniformity of the mixing to avoid local overheating or insufficient mixing. Then, the mixture is cooled to room temperature to form a solid wax sealing material. Finally, the wax sealing material is evenly coated on the amaryllis bulbs through a specific packaging device to form a protective film. The wax sealing material prepared by this method has a precisely controlled melting point and can adapt to the storage and transportation requirements under different ambient temperatures while keeping the amaryllis bulbs in good condition.

[0023] As for the technical solution of the present invention, another core element is to prepare a membrane structure that can be changed by relative humidity by using blending modification. In the present invention, the wax layer treated with wax sealing can be divided into two parts according to its structural function: a support layer and a separation layer. The support layer mainly composed of trimers forms an effective support structure with its excellent anti-swelling performance, while the separation layer is mainly composed of hexafluoropropylene dimers, and its molecular chain interaction force is weak. In a high humidity environment, the separation layer will slip, forming a creep effect, thereby reducing the molecular pores inside the wax sealing material, effectively blocking the penetration of water molecules, thereby achieving the dual effects of water retention and breathability. Hexafluoropropylene oligomers can be used as matrix materials and as fillers to improve the performance of other polymers. In view of the brittleness problem caused by uneven phase distribution and densification tendency of the blend, a multi-component blend was successfully prepared by introducing hexafluoropropylene oligomers as modifiers into the blending system. The blend achieves a combination of high tensile modulus and excellent ductility, significantly improving impact resistance. The wax sealing material of the present invention also has good biocompatibility and will not cause adverse effects on the growth of the corm of Amaryllis, that is, less fluorine diffusion occurs. Because in the preparation process of the oligomer, the present invention directional preparation constructs an oligomer with a higher trimer content, the trimer content can reach more than 72%, and the remaining dimer will form fluorine exchange in the process of mixing with paraffin, and the stability of fluorine in the incompletely fluorinated paraffin after fluorine exchange and the dimer after the molecular structure slip is further enhanced, thereby ensuring the stability of fluorine and the controllability of fluorine diffusion.

[0024] In practical applications, during the storage and transportation of the bulbs after wax sealing, the fluorine-containing wax sealing layer can also effectively resist the penetration and invasion of pathogens, reduce the risk of bulb rot, and thus improve the survival rate and planting efficiency of Amaryllis. At the same time, the wax sealing material is simple to use, easy to operate, and suitable for large-scale production and application. Through experimental verification, the wax sealing material of the present invention can maintain good stability and protective effect under different temperature and humidity conditions, and provides reliable technical support for the long-term storage and long-distance transportation of Amaryllis bulbs.

[0025] The beneficial effects of the present invention are: The present invention constructs a wax sealing material for amaryllis corms with good biocompatibility by directionally constructing oligomers and mixing the oligomers. The wax sealing material can play a good waterproof and antibacterial role as well as a mechanical protective role, while further optimizing the respiratory environment of the amaryllis corms, thereby improving its respiration and increasing the flowering rate and flowering period of the wax-sealed amaryllis. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0027] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0028] Example 1: A method for preparing a wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0029] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:4:0.04:0.02, and stirred at a speed of 100 r / min for 45 min under nitrogen atmosphere, temperature of 75 °C and pressure of 1.1 MPa to prepare hexafluoropropylene oligomer; The oligomer product was characterized and the conversion rate of hexafluoropropylene and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the conversion rate of hexafluoropropylene was 87.32% (the conversion rate of dimer and trimer of the target product), the dimer selectivity was 26.31%, and the trimer selectivity was 73.70% (the selectivity was calculated only based on the total amount of dimer and trimer); (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0030] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0031] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0032] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0033] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0034] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0035] The experimental and test results are shown in the following table.

[0036]

[0037] From the above characterization results, the wax sealing material of the present invention can significantly improve the respiratory environment of Amaryllis, thereby greatly increasing its flowering rate and average flowering period. Because more effective respiration can promote the transformation of substances, the plant growth condition is better and shows a significantly longer flowering period. The DGT characterization results show that although the wax sealing material of the present invention uses fluorine-containing raw materials, except for the contact residues on the epidermis, there is almost no diffusion. The fluorine diffusion phenomenon cannot be detected at 0.5mm below the skin, indicating that the wax sealing material of the present invention also shows very excellent biocompatibility.

[0038] On the other hand, the wax-sealing amaryllis of the experimental group and the wax-sealing amaryllis of the blank control group were immersed in clean water, and the water immersion height was about two-thirds of the height of the wax sealing layer. After immersion for 6 hours, the amaryllis were taken out and the mass change rate was characterized. The results showed that the change rate was ≤1%, indicating that the wax sealing material of the present invention has a waterproof property that is basically equivalent to that of the traditional wax sealing material.

[0039] Example 2: A method for preparing a wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0040] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:5:0.05:0.02, and stirred at a speed of 100 r / min for 45 min under a nitrogen atmosphere at a temperature of 75 °C and a pressure of 1.1 MPa to prepare a hexafluoropropylene oligomer; The oligomer product was characterized and the conversion rate of hexafluoropropylene and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the conversion rate of hexafluoropropylene was 86.83%, the dimer selectivity was 26.89%, and the trimer selectivity was 73.11%. (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0041] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0042] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0043] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0044] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0045] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0046] The experimental and test results are shown in the following table.

[0047]

[0048] Compared with Example 1, the amount of the oligomer used in this example is relatively increased, and the amount of polyethylene glycol and acetonitrile used in the oligomer is relatively increased. The selectivity of the trimer is slightly decreased during the preparation process, while in terms of overall product performance, the flowering rate and average flowering period are almost the same, and the air permeability and DGT characterization results are also basically the same. This shows that the wax sealing material product of the present invention has good performance stability.

[0049] Embodiment 3: A method for preparing a wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0050] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:6:0.06:0.02, and stirred at a speed of 100 r / min for 45 min under nitrogen atmosphere, temperature of 75 °C and pressure of 1.1 MPa to prepare hexafluoropropylene oligomer; The oligomer product was characterized and the conversion rate of hexafluoropropylene and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the conversion rate of hexafluoropropylene was 86.02%, the dimer selectivity was 27.71%, and the trimer selectivity was 72.29%; (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0051] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0052] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0053] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0054] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0055] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0056] The experimental and test results are shown in the following table.

[0057]

[0058] Compared with Example 1 and Example 2, this example further increases the amount of oligomers, and relatively increases the amount of polyethylene glycol and acetonitrile in the oligomers, showing a further decrease in trimer during the preparation process, and in terms of overall product performance, the flowering rate and average flowering period slightly decrease, while the air permeability and DGT characterization results are basically the same. This shows that the wax sealing material product of the present invention has good performance stability, but the amount of oligomers should not be too large, and the amount of acetonitrile and polyethylene glycol should also be controlled accordingly.

[0059] Comparative Example 1: A method for preparing a wax sealing material for Amaryllis bulbs. The specific preparation method is the same as that of Example 2. In the comparative example, only the catalyst for preparing hexafluoropropylene oligomers in the present invention is changed. Specifically, an equal amount of lithium fluoride is used as a substitute to prepare hexafluoropropylene oligomers, and the performance is tested by referring to the wax sealing experiment in Example 2. The specific characterization results and operation process are as follows.

[0060] A method for preparing wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0061] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and lithium fluoride were uniformly mixed in a mass ratio of 1.5:5:0.05:0.02, and stirred at a speed of 100 r / min for 45 min under a nitrogen atmosphere at a temperature of 75 °C and a pressure of 1.1 MPa to prepare a hexafluoropropylene oligomer; The oligomer product was characterized and the conversion rate of hexafluoropropylene and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the conversion rate of hexafluoropropylene was 71.37%, the dimer selectivity was 37.62%, and the trimer selectivity was 62.38%; (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0062] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0063] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0064] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0065] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0066] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0067] The experimental and test results are shown in the following table.

[0068]

[0069] Analysis of the above characterization data shows that the flowering rate in this example remains relatively good, while the oxygen permeability in the air permeability increases and the carbon dioxide permeability decreases, while the average flowering period has significantly decreased compared with Examples 1 to 3. Observation of the DGT characterization results shows that fluorine diffusion occurs. Combined with the analysis of the composition of the hexafluoropropylene oligomer in this example, it is found that the dimer component accounts for a large proportion of the hexafluoropropylene oligomer. The dimer may have a positive effect on expanding the respiratory pores, but when the dimer content accounts for too high a proportion, the slip will occur in advance and first inhibit the passage of larger carbon dioxide molecules, resulting in a polarized trend in the permeability change, and residual free fluorine atoms enter the plant, resulting in fluorine diffusion, and then the metabolism and other processes of the experimental group plants may be relatively affected. Although the flowering rate remains basically the same, this is mainly because the plant metabolic rate is higher after flowering, and the fluorine diffusion may be more intense or the impact is more significant.

[0070] Comparative Example 2: A method for preparing a wax sealing material for Amaryllis bulbs. The specific preparation method is the same as that of Example 2. In the comparative example, only the amount of polyethylene glycol used in the preparation process of the hexafluoropropylene oligomer in the present invention is adjusted to prepare the hexafluoropropylene oligomer. The specific characterization results and operation process are as follows.

[0071] A method for preparing wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0072] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:5:0.02:0.02, and stirred at a speed of 100 r / min for 45 min under a nitrogen atmosphere at a temperature of 75 °C and a pressure of 1.1 MPa to prepare a hexafluoropropylene oligomer; The oligomer product was characterized and the hexafluoropropylene conversion rate and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the hexafluoropropylene conversion rate was 69.87%, the dimer selectivity was 69.72%, and the trimer selectivity was 30.28%; (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0073] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0074] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0075] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0076] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0077] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0078] The experimental and test results are shown in the following table.

[0079]

[0080] Analyzing the above characterization data, in this example, when less polyethylene glycol is used, the product conversion rate and selectivity of the oligomers have undergone very significant changes, among which the selectivity of the dimer has increased dramatically while the selectivity of the trimer has decreased dramatically, and the final product test has shown very poor results, with its flowering rate and average flowering period being much lower than the data of Examples 1 to 3. The air permeability has also decreased significantly, which is also caused by the slippage and accumulation caused by the excessive dimer. In fact, in the early tests, the high proportion of dimers in the film did not cause a sharp drop in air permeability, but because of its slippage and layered accumulation, this led to the air permeability change trend of the wax sealing layer in the case of large thickness being different from that of the film. On the other hand, the increase in the content of dimers also significantly responded to the initial light of fluorine diffusion. Judging from the DGT characterization results, the degree of fluorine diffusion has increased significantly. This is similar to the results of the early PTFE test. In the early PTFE test, before the processed Amaryllis bulbs were wax-coated, a 0.5 mm thick PTFE film was coated on the bulb surface, and then wax-sealed using the current mature beeswax + paraffin process. The thickness of the beeswax layer was 2.7±0.1 cm, and the thickness of the paraffin layer was 7.3±0.1 cm. The results showed that the flowering rate and flowering period also decreased significantly. Similarly, the DGT characterization results detected fluorine diffusion in Ep0~Ep0.15. This shows that fluorine diffusion will have a significant impact on the growth and development process of wax-sealed Amaryllis.

[0081] Comparative Example 3: A method for preparing a wax sealing material for Amaryllis bulbs. The specific preparation method is the same as that of Example 2. In the comparative example, only the preparation environment of the hexafluoropropylene oligomer in the present invention is changed, specifically, the reaction temperature of the hexafluoropropylene trimer is changed. The specific characterization results and operation process are as follows.

[0082] A method for preparing wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0083] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:5:0.05:0.02, and stirred at a speed of 100 r / min for 45 min under a nitrogen atmosphere at a temperature of 30 °C and a pressure of 1.1 MPa to prepare a hexafluoropropylene oligomer; The oligomer product was characterized and the hexafluoropropylene conversion rate and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the hexafluoropropylene conversion rate was 71.20%, the dimer selectivity was 68.71%, and the trimer selectivity was 31.29%; (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0084] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0085] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0086] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0087] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0088] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0089] The experimental and test results are shown in the following table.

[0090]

[0091] Analyzing the above characterization data, the air permeability and other properties of the experimental group in this example have not been improved, and accompanied by more serious fluorine diffusion, the result is similar to that of comparative example 3, and the growth and metabolism of the experimental group plants are inhibited, which seriously affects the photosynthesis and respiration of the plants, interferes with the activity of various enzymes in the plants, and causes the experimental group plants to grow slowly, the leaves turn yellow, and even necrosis symptoms. It can be seen that temperature and polyethylene glycol have a greater impact on the directional construction of specific oligomers in the present invention, and have a huge impact on the performance of the sealing wax material.

[0092] Comparative Example 4: A method for preparing a wax sealing material for Amaryllis bulbs. The specific preparation method is the same as that of Example 2. In the comparative example, only the preparation environment of the hexafluoropropylene oligomer in the present invention is changed, specifically, the reaction temperature of the hexafluoropropylene trimer is changed. The specific characterization results and operation process are as follows.

[0093] A method for preparing wax sealing material for Amaryllis bulbs, The described amaryllis bulb wax sealing material comprises the following raw materials in percentage by weight:

[0094] The method comprises: (1) Liquid hexafluoropropylene, acetonitrile, polyethylene glycol and potassium fluoride were uniformly mixed in a mass ratio of 1.5:5:0.05:0.02, and stirred at a speed of 100 r / min for 45 min under a nitrogen atmosphere at a temperature of 90 °C and a pressure of 1.1 MPa to prepare a hexafluoropropylene oligomer; The oligomer product was characterized and the hexafluoropropylene conversion rate and the selectivity of dimer and trimer in this process were calculated. The characterization and calculation results showed that the hexafluoropropylene conversion rate was 79.33%, the dimer selectivity was 46.72%, and the trimer selectivity was 53.28%; (2) Hexafluoropropylene oligomer and beeswax were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.25 h under the environmental conditions of temperature of 95 °C, pressure of 0.3 MPa and stirring rate of 50 r / min to prepare the first stage mixture; (3) The first-stage mixed material and high melting point paraffin were mixed and stirred according to the above raw material ratio, and stirred and mixed for 1.5 h under the environmental conditions of temperature of 120 °C, pressure of 0.3 MPa, and stirring rate of 80 r / min to prepare the second-stage mixed material; (4) The second stage mixture and the viscosity enhancer were mixed according to the above raw material ratios, stirred at a temperature of 100 °C, a pressure of 0.3 MPa, and a stirring rate of 40 r / min for 0.6 h, and then cooled naturally to obtain the amaryllis bulb sealing wax material.

[0095] A wax sealing experiment was carried out on the wax sealing material prepared in this example.

[0096] Take mature amaryllis bulbs, cut off the leaves and roots, keep the bulbs, wash and disinfect the bulbs to get seed bulbs. In the disinfection process, use boiled water and 75% alcohol to dilute the disinfectant to get a 25% disinfectant, and soak the bulbs in the disinfectant. The bulbs are disinfected twice, each soaking time is 25 minutes, and the disinfectant is re-prepared before each soaking.

[0097] Coat the surface of the seed bulb with protective wax. Set a blank area 1.5 to 2.5 cm below the top of the bud of the bulb. The blank area does not need to be coated with protective wax (i.e. sealing wax material). Immerse the sterilized bulbs in 70 ℃ molten wax, then take them out, and repeat several times until the surface of the bulb is evenly coated with protective wax. Each immersion time is about 1 s, and repeat this process until a uniform protective wax layer is formed on the surface of the bulb, with a total thickness of about 10 mm. This is used as the experimental group.

[0098] After 105 days of simulated storage (including normal storage) at 8 ℃, the samples were taken out and placed in an environment where they could receive normal sunlight (sunny day sunshine duration of more than 7 hours) and the temperature was 20-22 ℃ for observation. The total number of flowers and flowering rate during the period from the first flowering sample to the time when the flowers withered were calculated, as well as the average flowering period of all flowering samples after the flowers withered. All samples were displayed and counted in the laboratory statistics or in the garden exhibition area in the same factory area with basically the same environment. Conventional wax-sealed amaryllis was used as a blank control for comparison. The storage and flowering environment of the blank control group were the same. Conventional wax-sealed amaryllis was wax-sealed using the currently mature beeswax + paraffin process, and the other treatments were the same, with a beeswax layer thickness of 2.7±0.1 cm and a paraffin layer thickness of 7.3±0.1 cm.

[0099] During the above wax sealing experiment, the wax sealing material was sent to a third-party university to test its oxygen and carbon dioxide permeability (the thickness and layer distribution were the same as those of the experimental group and the blank control group), and after the wax sealing experiment, two flowering samples and two non-flowering samples were taken (the sampling sites were the epidermis Ep0 after peeling off the wax sealing layer, Ep0.05 0.5 mm below the epidermis, Ep0.1 1.0 mm below the epidermis, and Ep0.15 1.5 mm below the epidermis, and 10 samples were taken from each site) and sent to a professional institution for DGT testing. The fluorine detection limit was 0.02 μg / g.

[0100] The experimental and test results are shown in the following table.

[0101]

[0102] Analyzing the above characterization data, the air permeability of the experimental group in this example was not significantly improved, and the performance of the growth and flowering period of Amaryllis was not significantly improved. Combined with the analysis of the composition of the hexafluoropropylene oligomer in this example, due to the high proportion of hexafluoropropylene dimer, the respiratory micropores formed by the cooperation and support of the fluorinated paraffin molecules and dimers were more, but early slippage occurred, resulting in poor optimization of the air permeability of paraffin, and the expected optimization effect was not achieved. Further comparative analysis of the data of the embodiment and comparative examples 3 and 4 shows the effect of temperature on the synthesis reaction of hexafluoropropylene trimer. At a lower reaction temperature, the conversion rate of the oligomer is low. In the temperature range of 75 to 85 ° C, as the temperature increases, the polymerization reaction rate is effectively accelerated, thereby promoting the conversion rate of hexafluoropropylene and the increase in the yield of hexafluoropropylene trimer. Within a specific temperature range, the increase in temperature can significantly promote the increase in the polymerization reaction rate. However, when the temperature continues to rise to more than 85 ℃, the reaction rate and the conversion rate of hexafluoropropylene both decrease significantly, and the relative content of hexafluoropropylene trimer in the polymerization product also decreases accordingly. The reason is that the polymerization process of hexafluoropropylene involves multiple chemical reactions, among which the reactions with higher activation energy tend to proceed at higher temperatures. Since the degree of polymerization of hexafluoropropylene trimer is higher than that of dimer, the increase in temperature is conducive to the formation of trimer in the temperature range of 75-85. However, when the temperature exceeds 85 ℃, the content of by-products in the polymerization product increases significantly, the reaction and composition of the oligomer become more complicated, and more impurities are produced, resulting in a decrease in the yield of hexafluoropropylene trimer.

Claims

1. A method for preparing a wax sealing material for Amaryllis bulbs, characterized in that: The method comprises: (1) The raw materials are prepared according to the following weight percentages: 33-37 wt% hexafluoropropylene oligomer, 4-6 wt% beeswax, 0.5-1.0 wt% tackifier, and the balance is high melting point paraffin; (2) mixing hexafluoropropylene oligomer and beeswax and stirring them to react to prepare a first-stage mixture; (3) mixing the first-stage mixed material with high-melting-point paraffin wax and stirring to react, thereby preparing a second-stage mixed material; (4) The second-stage mixed material and the viscosity enhancer are mixed evenly, and the mixture is cooled naturally to obtain the amaryllis bulb sealing wax material.

2. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 1, characterized in that: The hexafluoropropylene oligomer in step (1) is prepared by the following method: The perfluoro compound, nitrile compound, polymer and metal fluoride salt are uniformly mixed in proportion, and stirred and thermally reacted under high pressure conditions to obtain the directionally prepared hexafluoropropylene oligomer.

3. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 2, characterized in that: The perfluorinated compound is liquid hexafluoropropylene that has been subjected to a pressure treatment; The nitrile compound is acetonitrile; The polymer is polyethylene glycol; The metal fluoride salt is potassium fluoride; The perfluorinated compound, nitrile compound, polymer and metal fluoride salt are uniformly mixed in a mass ratio of 1.5:(4-6):(0.04-0.06):0.

02.

4. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 2 or 3, characterized in that: The high pressure condition is 1.0-1.2 MPa ambient pressure; The stirring thermal reaction is carried out at 75-85°C and 80-120 rpm for 40-45 min.

5. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 1, characterized in that: The mixing and stirring reaction in step (2) is carried out at 0.3-0.4 MPa, 95-105°C, and at a speed of 40-60 rpm for 45-75 min.

6. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 1, characterized in that: The mixing and stirring reaction in step (3) is carried out at 0.3-0.4 MPa, 120-140°C, and at a speed of 70-90 rpm for 60-90 min.

7. The method for preparing a wax sealing material for Amaryllis bulbs according to claim 1, characterized in that: The uniform mixing in step (4) is carried out by stirring and mixing at a speed of 30 to 50 rpm for 60 to 90 min under the conditions of 0.3 to 0.4 MPa and 100 to 120°C.

8. A wax sealing material for Amaryllis bulbs prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Flower arrangement device

    CN106395162A

  • Lily preservation method

    CN113207954A

  • Method for preparing hexafluoropropylene tripolymer by liquid phase method

    CN113912473A

  • Process for the production of protective coatings which prevent vegetative or animal colonisation and rodent or insect damage

    DE3522817A1

  • Process for preserving medicinal plants under vacuum.

    ES2107389A1